Mechanical properties and corrosion behavior of circular oscillating laser direct energy deposited nickel-based superalloy after different heat-treatment processes - Yelin Xia; Haoran Wu; Keyi Liu; Jianbo Lei; Yabao Hu; Hanning Chen; Chen Zheng (Journal of Materials Research and Technology)
Heat treatment can enhance the microstructure uniformity and mitigate element segregation in the nickel-based superalloy GH3536 fabricated via laser directional energy deposition, augmenting its mechanical and corrosion properties. This study used laser beam oscillation to deposit GH3536 specimens and designed three heat treatment regimens: solution treatment (1177 °C/1 h), aging treatment (720 °C/8 h), and solution + aging treatment (1177 °C/1 h + 720 °C/8 h). The regulatory mechanisms of the treatments on the microstructure, tensile fracture, and corrosion behavior of the alloy were investigated. After solid solution treatment, the microstructure was completely recrystallized, and the long striped Laves phase was dissolved and transformed into granules; After aging treatment, a large amount of carbides precipitated at the grain boundaries. After solution treatment, the microstructure was completely recrystallized, and the striped Laves phase is dissolved and transformed into granules, improving the solid-solution strengthening effect of the GH3536 alloy; After aging treatment, a large amount of carbides precipitate at the grain boundaries, which enhanced the strength of the GH3536 alloy through the pinning effect and weakened the toughness. After solid solution and aging treatment, the tensile strength of GH3536 alloy increased to 840 MPa, and the elongation exceeded 39%, which were 22.90% and 9.7% higher than that of the as-deposited GH3536 alloy, respectively; During electrochemical corrosion, solid solution treatment and solution + aging treatment lead to more uniform microstructure, facilitating the formation of denser passivation films and enhancing corrosion resistance. After aging treatment, dendritic microstructures and precipitates are prone to induce potential differences, undermining the corrosion resistance.